Relation of bronchoalveolar lavage T lymphocyte subpopulations to rate of regression of active pulmonary tuberculosis. Issue 8 (August 1995) - Yu, C T; Wang, C H; Huang, T J; Lin, H C; Kuo, H P
Abstract : BACKGROUND–Effective host defence against mycobacterial infection chiefly depends on the interactions between macrophages and T lymphocytes. This study investigated the relation of cellular components and their activity of cells obtained by bronchoalveolar lavage (BAL) from the lower respiratory tract to disease regression in patients with active pulmonary tuberculosis without HIV infection. METHODS–Clinical indices including age, sex, the presence of diabetes, fever, the presence of resistant strains of mycobacteria, the bacterial load in sputum, and disease extent on chest radiography at presentation were assessed before commencing four-drug antituberculous therapy. Twenty two patients with active pulmonary tuberculosis were divided into rapid, intermediate, and slow regression groups. Subpopulations of alveolar macrophages separated using discontinuous Percoll density gradient centrifugation and T lymphocytes (with CD3, CD4, CD8, and CD25 monoclonal antibodies) were quantified. RESULTS–There were no differences among rapid, intermediate, and slow regression groups in terms of age, sex, the presence of diabetes, the presence of resistant strains of mycobacteria, or the bacterial load in sputum. No differences were found between the groups in terms of subpopulations of alveolar macrophages or numbers of CD3 and CD4 lymphocytes. By contrast, an increase in CD8 cells was shown in the slow regression group compared with the rapid and intermediate regression groups. CD25 cell numbers were increased in the rapid regression group compared with the slow regression group. The CD4/CD8 ratio was decreased in the slow regression group compared with the rapid and intermediate regression groups and the relation between the proportion of CD25 cells and the CD4/CD8 ratio in BAL fluid was significant. CONCLUSIONS–A decreased CD4/CD8 ratio with an increase in CD8 cells in the alveolar spaces was associated with slow disease regression in patients with active pulmonary tuberculosis without HIV infection, suggesting that the balance of T lymphocyte subsets may play a central part in the modulation of host defence against mycobacterial infection.